Empowering Educators: A Comprehensive Human Resources: Framework for Improving Islamic-based Schools - Maulidatul Hasanah; Dinda Febrianti Putri; Khoirun Nisa'; Abu Hasan Agus R (Journal of Islamic Education Research, 2024)
This research aims to analyze human resource management strategies in Islamic-based schools. This research uses a qualitative case study type approach. Data collection techniques are carried out through interviews, observation, and documentation. Data analysis was carried out in stages, from data display to data reduction and concluding. Research shows that directed human resource management development can create an inclusive work environment, support cultural diversity, and improve employees' interpersonal skills. The implications of this research highlight the importance of directed human resource management in achieving socio-cultural harmony in organizations and provide an in-depth view of how human resource management can effectively achieve this goal. This research contributes to the practical and theoretical understanding of the importance of developing human resource management to improve socio-cultural competence in various organizational contexts.